Organic and Hybrid Materials for Photovoltaic and Photonic Applications - Virgili, Tersilla; Pasini, Mariacecilia (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Today, there is a huge demand for advanced materials capable of providing technological innovations. Among these, "organic semiconductors" combine the progress of semiconductors and plastic of the last century, becoming the subject of intense industrial and academic research. More recently, organic-inorganic hybrid functional materials have become a potential platform for applications in extremely diverse fields such as optics, microelectronics, transportation, health, energy, and energy storage. The interest in them is explained by the fact that it is possible to combine the best characteristics of both components in a large variety of combinations; in this way, they represent an intriguing class of materials with a large spectrum of applications.This reprint contribution will consider recent developments in the field of organic and hybrid materials in two of the most useful and promising applications of the millennium: photovoltaics and photonics. Multiple aspects of the materials will be taken into consideration, from the synthesis and the photophysical characterization to the application.